Body ownership and experiential ownership in the self-touching illusion - Liang, Caleb; Chang, Si-Yan; Chen, Wen-Yeo; Huang, Hsu-Chia; Lee, Yen-Tung (Frontiers in Psychology, 2015)
We investigate two issues about the subjective experience of one’s body: first, is the experience of owning a full-body fundamentally different from the experience of owning a body-part? Second, when I experience a bodily sensation, does it guarantee that I cannot be wrong about whether it is me who feels it? To address these issues, we conducted a series of experiments that combined the rubber hand illusion (RHI) and the “body swap illusion.” The subject wore a head mounted display (HMD) connected with a stereo camera set on the experimenter’s head. Sitting face to face, they used their right hand holding a paintbrush to brush each other’s left hand. Through the HMD, the subject adopted the experimenter’s first-person perspective (1PP) as if it was his/her own 1PP: the subject watched either the experimenter’s hand from the adopted 1PP, and/or the subject’s own hand from the adopted third-person perspective (3PP) in the opposite direction (180°), or the subject’s full body from the adopted 3PP (180°, with or without face). The synchronous full-body conditions generate a “self-touching illusion”: many participants felt that “I was brushing my own hand!” We found that (1) the sense of body-part ownership and the sense of full-body ownership are not fundamentally different from each other; and (2) our data present a strong case against the mainstream philosophical view called the immunity principle (IEM). We argue that it is possible for misrepresentation to occur in the subject’s sense of “experiential ownership” (the sense that I am the one who is having this bodily experience). We discuss these findings and conclude that not only the sense of body ownership but also the sense of experiential ownership call for further interdisciplinary studies.